A novel biointerface that suppresses cell morphological changes by scavenging excess reactive oxygen species. Issue 9 (26th February 2015) - Ikeda, Yutaka; Yoshinari, Tomoki; Nagasaki, Yukio
Abstract During cell cultivation on conventional culture dishes, various events results in strong stresses that lead to the production of bioactive species such as reactive oxygen species (ROS) and nitric oxide. These reactive species cause variable damage to cells and stimulate cellular responses. Here, we report the design of a novel biocompatible surface that decreases stress by not only morphologically modifying the dish surface by using poly(ethylene glycol) tethered chains, but also actively scavenging oxidative stress by using our novel nitroxide radical‐containing polymer. A block copolymer, poly(ethylene glycol)‐b‐poly[(2, 2, 6, 6‐tetramethylpiperidine‐N‐oxyl)aminomethylstyrene] (PEG‐b‐PMNT) was used to coat the surface of a dish. Differentiation of undifferentiated human leukemia (HL‐60) cells was found to be suppressed on the polymer‐coated dish. Notably, HL‐60 cell cultivation caused apoptosis under high‐density conditions, while spontaneous apoptosis was suppressed in cells plated on the PEG‐b‐PMNT‐modified surface, because a healthy mitochondrial membrane potential was maintained. In contrast, low molecular weight antioxidants did not have apparent effects on the maintenance of mitochondria. We attribute this to the lack of cellular internalization of our immobilized polymer and selective scavenging of excessive ROS generated outside of cells. These results demonstrate the utility of our novel biocompatible material for actively scavenging ROS and thus maintaining cellular morphology. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2815–2822, 2015.